Komponen Sindrom Metabolik sebagai Faktor Risiko Penyakit Ginjal Kronik Stadium Terminal (Studi di RSUP Dr.Kariadi dan RSUD Kota Semarang) - Kartika Ikawati; Shofa Chasani; Suhartono Suhartono; Suharyo Hadisaputro; Selamat Budijitno (Jurnal Epidemiologi Kesehatan Komunitas, 2018)
Background: End Stage Renal Disease (ESRD) has been among the top ten list of non infectious diseases frequently found at RSUP dr. Kariadi and RSUD Kota Semarang. Risk factors for ESRD are metabolic syndrome components, which are having an upward trend. This study had an objective to provided an evidence of metabolic syndrome factors that became risk factors for ESRD.Method: This study applied an analytical observational method with a case control study design. The study used 90 respondents as samples, divided into two different groups: 45 respondents as case samples and 45 respondents as control samples with consecutive sampling. Variables in this study ware the individual characteristics and history of suffering from metabolic syndrome components. Data were collected by interview, medical record, and indepth interview. These data were subject to analyses using univariat, bivariate, and multivariate tests.Results: The study found the risk factors for ESRD as the followings: hypertension term of> 5 years (OR=10,89 and 95% CI=3,08-38,59; p=0,000), diabetes mellitus term of > 5 years (OR=3,84; 95% CI=1,20-12,30; p=0,023), and low HDL-cholesterol history of < 35 mg/dL(men) and < 40 mg/dL(women) with (OR=3.123, 95% CI=1.08-9.04; p=0,04). The indepth interview resulted in adequate knowledge of the respondents about the risk factors for ESRD.Conclusion: Risk factors for ESRD found during the observation were hypertension term of >5 years, diabetes mellitus term of >5 years, and low cholesterol HDL. To prevent theprogression of chronik kidney disease required strict control of metabolic syndrome.